METAVERSES, ARTIFICIAL INTELLIGENCE AND CHALLENGES TO PSYCHOLOGICAL SECURITY - Pashentsev, Evgeny; Sebekin, Sergey (The Policy of National Security, 2023)
Today, the rapid development of the fourth industrial revolution and the emergence of the latest digital technologies leads to the gradual creation of a fundamentally new "socio-technological" reality – a metaverse that will permeate all levels of society and human existence: socio-social relations, economics, political processes, thus influencing the psychology of human consciousness and perception of reality. The existence, full functioning of this new "Reality 2.0" and its convergence with the physical world will be provided by a wide range of new technologies, one of which is "advanced" artificial intelligence (AI) systems, which will underlie the basis of the creation of the metaverse architecture itself and be used for 3D modeling, creation of digital objects, design and expansion virtual worlds-clusters, data analysis, etc.At the same time, metaverses implementing technologies of full immersion in virtual reality are able to release conflict potential and create a wide range of opportunities for ultimate antisocial impact on social processes, social groups and individuals through specific forms of malicious use of AI in order to undermine psychological stability (PS). The article will consider specific technologies of influencing the consciousness of users through AI. Special attention will be paid to how the use of AI systems in metaverses can produce local and global threats to psychological stability, and through that to political, economic, military institutions.The relevance of the paper is due to the growing popularity of the phenomenon of metaverses and growing number of users ("meta-citizens"), increased investments in this area and the development of AI technologies that make the experience of being in the metaverses more immersive, which in turn makes users most vulnerable to HT psychological influences. Today, at the level of states, international institutions and global forums, the importance of regulating the new reality and creating a safe metaverse is being stated, which makes it necessary to study possible options for negative effects on consciousness through AI technologies and consider ways to counter these threats. At the same time, there is a lack of studies in this area, that negatively affects the level of expert assessments, the effectiveness of decision-making and, more broadly, the level of awareness of the general public about the nature and size of emerging threats. The paper aims to close this gap whenever possible and contribute to a broader discussion on this hot issue.
Keywords: metaverses; malicious use of artificial intelligence; psychological security; social polarization; digital discrimination